PARIWISATA HALAL : PERLUKAH REKONSEPTUALISASI? - Akhmad Saufi; Lalu Edy Herman Mulyono; Idham Kholid; Herman Jayadi; Siti Hamdiah Hamdiah Rojabi; Ega Dwi Putri M; Baiq Lisdiana Apriani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
The purpose of this study was to understand perceptions and attitudes of tourism communities towards halal tourism terminology and the development of tourism based on local wisdom. This research adopted qualitative research and was conducted in Lombok. Data was collected in three main tourist destinations including Kuta, Senggigi and Gili Trawangan, therough in-depth interviews and observations, and was analysed using content analysis. The results indicate that tourism businessmen and foreign tourists have a good perception towards the concept of halal tourism and support the development of tourism based on local wisdom. Yet, both informant groups have different opinion towards the use of “halal tourism” as a terminology to promote halal tourism products. Therefore, a systematic socialization on halal tourism is needed to develop consensus among all tourism stakeholders.Keywords: Halal Tourism, Perception, Local Wisdom, Consensus, tourism communities